Epidermal and adnexal tumors. - Bonifazi, E.; Tarantino, G. (European Journal of Pediatric Dermatology, 2000)
Basal cell carcinoma is a tumor deriving from keratinocytes. It is characterized by a differentiation that is reminiscent of keratinocytes of the basal layer. Basal cell carcinoma is a low malignancy tumor and only exceptionally gives raise to metastases. It affects subjects even with dark phototype, mainly on photoexposed areas, but even on other sites, starting from the third decade of life. Exceptionally, basal cell carcinoma affects subjects under 20 (4, 9, 17, 29), almost always due to predisposing factors. The latter include xeroderma pigmentosum, sebaceous nevus, nevoid basal-cell carcinoma syndrome, and chronic muco-cutaneous candidiasis. (...).